Water-based paint based on modified acrylic resin and preparation method of water-based paint
By using core-shell acrylate and four-layer core-shell structure crosslinking agent in aqueous coatings, combined with modified silica and aminolated graphene oxide, the performance of water-based coatings in high temperature resistance, corrosion resistance and flame retardant is solved. The problem of insufficient has significantly improved its mechanical properties and adhesion, meeting a wider range of application needs.
Patent Information
- Application Number
- CN202411399952.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-09
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-10-09
AI Technical Summary
Existing water-based coatings have insufficient performance in terms of high temperature resistance, corrosion resistance and flame retardant, and have poor adhesion and wear resistance, which affects their application breadth and service life.
Using water-based coatings based on modified acrylic resin and preparation method, by mixing core-shell acrylic acid ester and aqueous acrylic resin as the base emulsion, and introducing a crosslinking agent with four-layer core-shell structure, using modified silica and Aminized graphene oxide and other materials to improve the damping performance, corrosion resistance and mechanical properties of the coating.
It significantly improves the damping performance, corrosion resistance, tensile strength, impact strength and hardness of water-based coatings, enhances its adhesion and flame retardant properties, and meets a wider range of application needs.
Smart Images

Figure BDA0005074983100000211 
Figure BDA0005074983100000212 
Figure BDA0005074983100000213
Abstract
Description
Technical Field
[0001] The invention relates to the field of coating preparation, and in particular to a water-based coating based on modified acrylic resin and a preparation method thereof. Background Art
[0002] With the rapid development of science and technology and the continuous improvement of living standards, people's environmental awareness is also increasing. This has gradually caused people to pay attention to and attach importance to material safety issues. At the same time, the performance requirements for coatings are getting higher and higher. Traditional solvent-based coatings are mainly composed of fillers, binders, organic solvents and additives. A large amount of volatile organic compounds will be released during the production and use process. These compounds will not only pollute the environment, but also may cause harm to human health. Water-based coatings are coatings that use water as a solvent or a dispersion medium. In addition to the excellent performance of solvent-based coatings, they also have the advantages of simple use, non-toxicity, and no environmental pollution. They are widely used in buildings, industrial products, automobiles, packaging and printing and other industries. However, water-based coatings are often difficult to meet the requirements in terms of high temperature resistance, corrosion resistance and flame retardancy.
[0003] Silicone has the advantages of good insulation, corrosion resistance, high temperature resistance, flame retardancy, and easy processing. It is an ideal modified material for improving the performance of water-based coatings. By introducing silicone, the comprehensive performance of water-based coatings can be significantly enhanced to meet the application needs of a wider range of fields. However, the current silicone-modified water-based coatings have the disadvantages of poor adhesion and wear resistance. If the adhesion of the coating is insufficient, the coating is prone to peeling or cracking, which not only affects the aesthetics of the coating, but is also likely to cause the coating to lose effective protection of the substrate. In addition, when the coating is subjected to friction or external force, it is prone to wear and peeling, which may cause the coating to become mottled and uneven, lose its original gloss, increase maintenance costs, and shorten its service life.
[0004] The patent with publication number CN109504267B discloses a silicone-modified water-based composite wood coating, and its preparation method and application. Silicone is introduced into polyacrylate and water-based polyurethane by a chemical modification method, so that the active siloxane groups in their structure are hydrolyzed under certain conditions to form silanols, which can be dehydrated and condensed to form a three-dimensional network cross-linked structure, thereby increasing the cross-linking density of the polymer. The coating prepared by this invention has the advantages of good hardness and good heat resistance, but the water-based coating prepared by this method has poor damping performance and poor corrosion resistance.
[0005] Therefore, according to the above-mentioned related technologies, it is urgent to develop a water-based coating based on modified acrylic resin and a preparation method thereof. Summary of the invention
[0006] In view of this, the purpose of the present invention is to provide a water-based coating based on modified acrylic resin and a preparation method thereof, so as to solve the problem of poor corrosion resistance of acrylic resin water-based coatings in the prior art.
[0007] Based on the above purpose, the present invention provides a water-based coating based on modified acrylic resin and a preparation method thereof.
[0008] A water-based coating based on modified acrylic resin, comprising the following raw materials in parts by weight: 100-105 parts of a base emulsion, 8-12 parts of a cross-linking agent, 0.5-0.8 parts of triethanolamine, 0.4-0.8 parts of a defoaming agent, and 0.3-0.6 parts of a wetting and dispersing agent;
[0009] The base emulsion is obtained by mixing water-based acrylic resin and core-shell acrylic ester in a mass ratio of 80-85:15-20;
[0010] The crosslinking agent is a four-layer core-shell structure, and the four-layer core-shell structure is prepared by a core layer emulsion, an inner layer emulsion, an intermediate layer emulsion and an outer layer emulsion;
[0011] The core layer emulsion is prepared from modified silicon dioxide;
[0012] The inner layer emulsion is prepared from methyl methacrylate and styrene;
[0013] The intermediate layer emulsion is prepared from butyl acrylate, methyl methacrylate and modified graphene;
[0014] The outer layer emulsion is prepared from butyl acrylate, methyl methacrylate and styrene;
[0015] The modified graphene is amino-modified graphene oxide.
[0016] Preferably, the preparation process of the basic emulsion is as follows:
[0017] Step A1. Methyl methacrylate, styrene, a crosslinking agent and deionized water are mixed evenly, an emulsifier is added, and pre-emulsification is carried out at 70-75° C. for 28-32 minutes at a speed of 280-300 r / min, and then an initiator is added and reacted for 150-160 minutes to obtain a mixed solution A;
[0018] Step A2. Mix butyl acrylate and isooctyl acrylate evenly, add an initiator, and mix evenly to obtain a mixed solution B;
[0019] Step A3. Add the mixed solution A dropwise to the mixed solution B at a flow rate of 1.8-2.2 r / min. After the addition is completed, continue the reaction for 150-160 min to obtain a core-shell type acrylate.
[0020] Preferably, the usage ratio of methyl methacrylate, styrene, crosslinking agent, deionized water, emulsifier and initiator in step A1 is 6-9 g: 6-9 g: 0.15-0.45 g: 40-50 mL: 0.11-0.16 g: 0.08-0.12 g;
[0021] The cross-linking agent in step A1 is divinylbenzene;
[0022] The emulsifier in step A1 is any one of an anionic emulsifier and a nonionic emulsifier;
[0023] The anionic emulsifier is sodium dodecyl sulfate, and the nonionic emulsifier is OP-10;
[0024] The initiator in step A1 is ammonium persulfate.
[0025] Preferably, the usage ratio of butyl acrylate, octyl acrylate and initiator in step A2 is 26-31 g: 4-7 g: 0.35-1.05 g;
[0026] The initiator in step A2 is ammonium persulfate;
[0027] The mass ratio of the mixed solution A to the mixed solution B in step A3 is 28-32:68-72.
[0028] Preferably, the preparation process of the cross-linking agent is as follows:
[0029] Step B1. Add nano-silica to an ethanol aqueous solution, add KH570 after uniform dispersion, and then add oxalic acid to adjust the pH to 4, react at 68-72°C for 110-120min, filter, and wash with ethanol to obtain modified silica;
[0030] Step B2. Add modified silica, butyl acrylate, styrene and a crosslinking agent to deionized water, add an emulsifier, place at 65-70 ° C for 30-35 minutes under nitrogen protection to obtain a pre-emulsification solution, then add an initiator, and react at a stirring speed of 280-300 r / min for 150-160 minutes to obtain an inner layer emulsion;
[0031] Step B3. Add an initiator to the inner layer emulsion, and drip butyl acrylate, methyl methacrylate and a crosslinking agent therein using a peristaltic pump at a flow rate of 1.8-2.2 r / min. After the dripping is completed, continue the polymerization reaction for 150-160 min to obtain an intermediate layer pre-emulsion;
[0032] Step B4. dispersing graphene oxide in deionized water to obtain a graphene oxide dispersion, adding a silane coupling agent to anhydrous ethanol, and dispersing uniformly by ultrasonication for 5-7 minutes to obtain a silane coupling agent dispersion, ultrasonically mixing the graphene oxide dispersion and the silane coupling agent dispersion, reacting in an oil bath at 78-86° C. for 6-8 hours, and centrifuging for standby use to obtain functionalized graphene;
[0033] Step B5. The pH of the intermediate layer pre-emulsion is adjusted to 8-9, functionalized graphene is added, and the intermediate layer emulsion is obtained after ultrasonic treatment for 30-50 minutes;
[0034] Step B6. Add an initiator to the middle layer emulsion and drop butyl acrylate, methyl methacrylate, styrene and hydroxyethyl methacrylate using a peristaltic pump at a flow rate of 1.8-2.2 r / min. After the dropwise addition is completed, continue the polymerization reaction for 150-160 minutes to obtain a crosslinking agent.
[0035] Preferably, the usage ratio of the nano-silica, ethanol aqueous solution and KH570 in step B1 is 0.3-0.6 g: 10-14 mL: 0.035-0.045 g;
[0036] The volume fraction of the ethanol aqueous solution in step B1 is 78%-82%;
[0037] The amount ratio of modified silica, butyl acrylate, styrene, crosslinking agent, deionized water, emulsifier and initiator in step B2 is 1.5-2g: 1.2-4.2g: 10.11-13.8g: 0.6-0.9g: 36-42mL: 0.4-0.7g: 0.5-0.8g;
[0038] The cross-linking agent in step B2 is divinylbenzene;
[0039] The emulsifier in step B2 is obtained by mixing an anionic emulsifier and a nonionic emulsifier in a mass ratio of 0.2-0.4:0.2-0.3;
[0040] In step B2, the anionic emulsifier is sodium dodecyl sulfate, and the nonionic emulsifier is OP-10;
[0041] The initiator in step B2 is ammonium persulfate.
[0042] Preferably, the usage ratio of the inner layer emulsion, initiator, butyl acrylate, methyl methacrylate and crosslinking agent in step B3 is 40-42 mL: 0.2-0.4 g: 12-14 g: 15.3-18 g: 0.4-0.7 g;
[0043] The initiator in step B3 is ammonium persulfate;
[0044] The cross-linking agent in step B3 is divinylbenzene.
[0045] Preferably, the ratio of graphene oxide to deionized water in step B4 is 3-6 g: 100-105 mL;
[0046] The usage ratio of the silane coupling agent and anhydrous ethanol in step B4 is 5-9 g: 80-85 mL;
[0047] The volume ratio of the graphene oxide dispersion and the silane coupling agent dispersion in step B4 is 100-105:80-85;
[0048] The silane coupling agent in step B4 is KH-550.
[0049] Preferably, the ratio of the intermediate layer pre-emulsion to the functionalized graphene in step B5 is 38-42 mL: 0.1-0.2 g;
[0050] The usage ratio of the intermediate layer emulsion, initiator, butyl acrylate, methyl methacrylate, styrene and hydroxyethyl methacrylate in step B6 is 40-42 mL: 0.3-0.6 g: 16-23 g: 5-9 g: 5-7 g: 0.45-1.35 g;
[0051] The initiator in step B6 is ammonium persulfate.
[0052] A method for preparing a water-based coating based on a modified acrylic resin comprises the following steps:
[0053] The base emulsion, the crosslinking agent, the triethanolamine, the defoaming agent and the wetting and dispersing agent are uniformly mixed to obtain a water-based coating based on the modified acrylic resin.
[0054] Beneficial effects of the present invention:
[0055] The present invention provides a water-based coating based on modified acrylic resin and a preparation method thereof. The present invention uses a core-shell type acrylate and a water-based acrylic resin as a base emulsion, wherein the core-shell type acrylate can increase the uniform dispersion inside the system on the one hand, and can also improve the damping performance and corrosion resistance of the water-based coating on the other hand.
[0056] The invention provides a water-based coating based on modified acrylic resin and a preparation method thereof. The invention introduces an acrylic polymer with a four-layer core-shell structure as a crosslinking agent into a system, wherein the multi-layer core-shell structure can toughen and modify the water-based acrylic resin, and the core-shell structure can be uniformly dispersed in the system, and the various aromatic ring rigid structures contained therein can effectively improve the tensile strength, impact strength and hardness of the water-based coating. In addition, the water-based coating can also have higher flame retardant properties, and further interact with a basic emulsion to enhance the damping performance while further improving the corrosion resistance. DETAILED DESCRIPTION
[0057] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments.
[0058] The sources and properties of some of the raw materials used in the present invention are as follows:
[0059] The solid content of water-based acrylic resin is 45%, and the model is CFW905F;
[0060] The brand of defoamer is Efka SI 2741;
[0061] The grade of the wetting and dispersing agent is AFCONA-5207.
[0062] Embodiment 1: A method for preparing a water-based coating based on a modified acrylic resin, comprising the following steps:
[0063] S1. 6 g of methyl methacrylate, 6 g of styrene, 0.15 g of divinylbenzene and 40 mL of deionized water were mixed evenly, 0.11 g of sodium dodecyl sulfate was added, pre-emulsified at 70 ° C for 28 min at a speed of 280 r / min, and then 0.08 g of ammonium persulfate was added and reacted for 150 min to obtain a mixed solution A;
[0064] S2. 26 g of butyl acrylate and 4 g of isooctyl acrylate were mixed, 0.35 g of ammonium persulfate was added, and mixed to obtain a mixed solution B;
[0065] S3. 28 g of the mixed solution A was added dropwise to 68 g of the mixed solution B at a flow rate of 1.8 r / min. After the addition was completed, the reaction was continued for 150 min to obtain a core-shell acrylate;
[0066] S4. 80 g of an aqueous acrylic resin and 15 g of a core-shell acrylate were mixed to obtain a base emulsion;
[0067] S5. 0.3 g of nano-silica was added to 10 mL of 78% ethanol aqueous solution, and after being evenly dispersed, 0.035 g of KH570 was added, and then oxalic acid was added dropwise to adjust the pH to 4, and the reaction was carried out at 68 ° C for 110 min, filtered, and washed with ethanol to obtain modified silica;
[0068] S6. 0.2 g of sodium dodecyl sulfate and 0.2 g of OP-10 were mixed to obtain an emulsifier;
[0069] S7. 1.5 g of modified silica, 1.2 g of butyl acrylate, 10.11 g of styrene and 0.6 g of divinylbenzene were added to 36 mL of deionized water, 0.4 g of emulsifier was added, and pre-emulsified at 65 ° C for 30 min under nitrogen protection to obtain a pre-emulsion, and then 0.5 g of ammonium persulfate was added, and the reaction was carried out at a stirring speed of 280 r / min for 150 min to obtain an inner emulsion;
[0070] S8. 0.2 g of ammonium persulfate was added to 40 mL of the inner emulsion, and 12 g of butyl acrylate, 15.3 g of methyl methacrylate and 0.4 g of divinylbenzene were dropped thereinto by a peristaltic pump at a flow rate of 1.8 r / min. After the addition was completed, the polymerization reaction was continued for 150 min to obtain an intermediate layer pre-emulsion;
[0071] S9. 3 g of graphene oxide was dispersed in 100 mL of deionized water to obtain a graphene oxide dispersion, and then 5 g of KH-550 was added to 80 mL of anhydrous ethanol, and the dispersion was uniformly dispersed by ultrasonication for 5 min to obtain a silane coupling agent dispersion, and 100 mL of the graphene oxide dispersion and 80 mL of the silane coupling agent dispersion were uniformly mixed by ultrasonication, reacted in an oil bath at 78° C. for 6 h, and centrifuged for standby use to obtain functionalized graphene;
[0072] S10. The pH of 38 mL of the intermediate layer pre-emulsion was adjusted to 8, 0.1 g of functionalized graphene was added, and the intermediate layer emulsion was obtained after ultrasonic treatment for 30 min;
[0073] S11. 0.3 g of ammonium persulfate was added to 40 mL of the intermediate layer emulsion and 16 g of butyl acrylate, 5 g of methyl methacrylate, 5 g of styrene and 0.45 g of hydroxyethyl methacrylate were added dropwise using a peristaltic pump at a flow rate of 1.8 r / min. After the addition was completed, the polymerization reaction was continued for 150 min to obtain a crosslinker;
[0074] S12. 80 g of an aqueous acrylic resin and 15 g of a core-shell acrylate were mixed to obtain a base emulsion;
[0075] S13. 100 g of the base emulsion, 8 g of the cross-linking agent, 0.5 g of triethanolamine, 0.4 g of the defoaming agent, and 0.3 g of the wetting and dispersing agent were mixed uniformly to obtain a water-based coating based on a modified acrylic resin.
[0076] Embodiment 2: A method for preparing a water-based coating based on a modified acrylic resin, comprising the following steps:
[0077] S1. 6.6 g of methyl methacrylate, 6.6 g of styrene, 0.25 g of divinylbenzene and 42 mL of deionized water were mixed evenly, 0.12 g of OP-10 was added, pre-emulsified at 71 ° C at a speed of 285 r / min for 29 min, and then 0.09 g of ammonium persulfate was added and reacted for 152 min to obtain a mixed solution A;
[0078] S2. 27 g of butyl acrylate and 5 g of isooctyl acrylate were mixed, 0.5 g of ammonium persulfate was added, and mixed to obtain a mixed solution B;
[0079] S3. 29 g of the mixed solution A was added dropwise to 69 g of the mixed solution B at a flow rate of 1.9 r / min. After the addition was completed, the reaction was continued for 152 min to obtain a core-shell acrylate;
[0080] S4. 81 g of an aqueous acrylic resin and 16 g of a core-shell acrylate were mixed to obtain a base emulsion;
[0081] S5. 0.4 g of nano-silica was added to 11 mL of 79% ethanol aqueous solution, and after being evenly dispersed, 0.038 g of KH570 was added, and then oxalic acid was added dropwise to adjust the pH to 4, and the reaction was carried out at 69 ° C for 112 min, filtered, and washed with ethanol to obtain modified silica;
[0082] S6. 0.3 g of sodium dodecyl sulfate and 0.22 g of OP-10 were mixed to obtain an emulsifier;
[0083] S7. 1.6 g of modified silica, 2 g of butyl acrylate, 11 g of styrene and 0.7 g of divinylbenzene were added to 37 mL of deionized water, 0.5 g of emulsifier was added, and pre-emulsified at 66 ° C for 31 min under nitrogen protection to obtain a pre-emulsion, and then 0.6 g of ammonium persulfate was added, and the reaction was carried out at a stirring speed of 284 r / min for 152 min to obtain an inner emulsion;
[0084] S8. 0.3 g of ammonium persulfate was added to 41 mL of the inner emulsion, and 13 g of butyl acrylate, 16 g of methyl methacrylate and 0.5 g of divinylbenzene were dropped thereinto by a peristaltic pump at a flow rate of 1.9 r / min. After the addition was completed, the polymerization reaction was continued for 152 min to obtain an intermediate layer pre-emulsion;
[0085] S9. 4 g of graphene oxide was dispersed in 101 mL of deionized water to obtain a graphene oxide dispersion, and 6 g of KH-550 was added to 81 mL of anhydrous ethanol, and the dispersion was uniformly dispersed by ultrasonic treatment for 6 min to obtain a silane coupling agent dispersion, and 101 mL of the graphene oxide dispersion and 81 mL of the silane coupling agent dispersion were uniformly mixed by ultrasonic treatment, reacted in an oil bath at 80° C. for 7 h, and centrifuged for standby use to obtain functionalized graphene;
[0086] S10. The pH of 39 mL of the intermediate layer pre-emulsion was adjusted to 8.5, 0.12 g of functionalized graphene was added, and the intermediate layer emulsion was obtained after ultrasonic treatment for 34 min;
[0087] S11. 0.4 g of ammonium persulfate was added to 41 mL of the intermediate layer emulsion and 18 g of butyl acrylate, 6 g of methyl methacrylate, 6 g of styrene and 0.6 g of hydroxyethyl methacrylate were added dropwise using a peristaltic pump at a flow rate of 1.9 r / min. After the addition was completed, the polymerization reaction was continued for 152 min to obtain a crosslinker;
[0088] S12. 81 g of an aqueous acrylic resin and 16 g of a core-shell acrylate were mixed to obtain a base emulsion;
[0089] S13. 101 g of the base emulsion, 9 g of the cross-linking agent, 0.6 g of triethanolamine, 0.5 g of the defoaming agent, and 0.4 g of the wetting and dispersing agent were mixed uniformly to obtain a water-based coating based on a modified acrylic resin.
[0090] Embodiment 3: A method for preparing a water-based coating based on a modified acrylic resin, comprising the following steps:
[0091] S1. 7 g of methyl methacrylate, 7 g of styrene, 0.3 g of divinylbenzene and 44 mL of deionized water were mixed evenly, 0.13 g of sodium dodecyl sulfate was added, pre-emulsified at 72 ° C for 30 min at a speed of 290 r / min, and then 0.1 g of ammonium persulfate was added and reacted for 154 min to obtain a mixed solution A;
[0092] S2. 28 g of butyl acrylate and 6 g of isooctyl acrylate were mixed, 0.6 g of ammonium persulfate was added, and mixed to obtain a mixed solution B;
[0093] S3. 30 g of the mixed solution A was added dropwise to 70 g of the mixed solution B at a flow rate of 2 r / min, and the reaction was continued for 154 min after the addition was completed to obtain a core-shell acrylate;
[0094] S4. 82 g of an aqueous acrylic resin and 17 g of a core-shell acrylate were mixed to obtain a base emulsion;
[0095] S5. 0.5 g of nano-silica was added to 12 mL of 80% ethanol aqueous solution, and after being evenly dispersed, 0.04 g of KH570 was added, and then oxalic acid was added dropwise to adjust the pH to 4, and the reaction was carried out at 70 ° C for 114 min, filtered, and washed with ethanol to obtain modified silica;
[0096] S6. 0.4 g of sodium dodecyl sulfate and 0.24 g of OP-10 were mixed to obtain an emulsifier;
[0097] S7. 1.7 g of modified silica, 2.6 g of butyl acrylate, 12 g of styrene and 0.8 g of divinylbenzene were added to 38 mL of deionized water, 0.6 g of emulsifier was added, and pre-emulsified at 67 ° C for 32 min under nitrogen protection to obtain a pre-emulsion, and then 0.7 g of ammonium persulfate was added, and the reaction was carried out at a stirring speed of 288 r / min for 154 min to obtain an inner emulsion;
[0098] S8. 0.4 g of ammonium persulfate was added to 42 mL of the inner emulsion, and 14 g of butyl acrylate, 16.5 g of methyl methacrylate and 0.6 g of divinylbenzene were dropped thereinto by a peristaltic pump at a flow rate of 2 r / min. After the addition was completed, the polymerization reaction was continued for 154 min to obtain an intermediate layer pre-emulsion;
[0099] S9. 5 g of graphene oxide was dispersed in 102 mL of deionized water to obtain a graphene oxide dispersion, and 7 g of KH-550 was added to 82 mL of anhydrous ethanol, and the dispersion was uniformly dispersed by ultrasonic treatment for 7 min to obtain a silane coupling agent dispersion, and 102 mL of the graphene oxide dispersion and 82 mL of the silane coupling agent dispersion were uniformly mixed by ultrasonic treatment, reacted in an oil bath at 82° C. for 8 h, and centrifuged for standby use to obtain functionalized graphene;
[0100] S10. The pH of 40 mL of the intermediate layer pre-emulsion was adjusted to 9, 0.14 g of functionalized graphene was added, and the intermediate layer emulsion was obtained after ultrasonic treatment for 38 min;
[0101] S11. 0.5 g of ammonium persulfate was added to 42 mL of the intermediate layer emulsion and 20 g of butyl acrylate, 7 g of methyl methacrylate, 7 g of styrene and 0.75 g of hydroxyethyl methacrylate were added dropwise using a peristaltic pump at a flow rate of 2.1 r / min. After the addition was completed, the polymerization reaction was continued for 154 min to obtain a crosslinker;
[0102] S12. 82 g of an aqueous acrylic resin and 17 g of a core-shell acrylate were mixed to obtain a base emulsion;
[0103] S13. 102 g of the base emulsion, 10 g of a cross-linking agent, 0.7 g of triethanolamine, 0.6 g of a defoaming agent, and 0.5 g of a wetting and dispersing agent were mixed uniformly to obtain a water-based coating based on a modified acrylic resin.
[0104] Embodiment 4: A method for preparing a water-based coating based on a modified acrylic resin, comprising the following steps:
[0105] S1. 8 g of methyl methacrylate, 8 g of styrene, 0.35 g of divinylbenzene and 46 mL of deionized water were mixed evenly, 0.14 g of OP-10 was added, pre-emulsified at 73 ° C for 31 min at a speed of 295 r / min, and then 0.11 g of ammonium persulfate was added and reacted for 156 min to obtain a mixed solution A;
[0106] S2. 29 g of butyl acrylate and 5 g of isooctyl acrylate were mixed, 0.8 g of ammonium persulfate was added, and mixed to obtain a mixed solution B;
[0107] S3. 31 g of the mixed solution A was added dropwise to 71 g of the mixed solution B at a flow rate of 2.1 r / min. After the addition was completed, the reaction was continued for 156 min to obtain a core-shell acrylate;
[0108] S4. 83 g of an aqueous acrylic resin and 18 g of a core-shell acrylate were mixed to obtain a base emulsion;
[0109] S5. 0.4 g of nano-silica was added to 12 mL of an ethanol aqueous solution having a volume fraction of 81%, and after being evenly dispersed, 0.042 g of KH570 was added, and then oxalic acid was added dropwise to adjust the pH to 4, and the reaction was carried out at 71 ° C for 116 min, filtered, and washed with ethanol to obtain modified silica;
[0110] S6. 0.2 g of sodium dodecyl sulfate and 0.26 g of OP-10 were mixed to obtain an emulsifier;
[0111] S7. 1.8 g of modified silica, 3 g of butyl acrylate, 12.5 g of styrene and 0.8 g of divinylbenzene were added to 39 mL of deionized water, 0.7 g of emulsifier was added, and pre-emulsified at 68 ° C for 33 min under nitrogen protection to obtain a pre-emulsion, and then 0.8 g of ammonium persulfate was added, and the reaction was carried out at a stirring speed of 292 r / min for 154 min to obtain an inner emulsion;
[0112] S8. 0.2 g of ammonium persulfate was added to 40 mL of the inner emulsion, and 12 g of butyl acrylate, 17 g of methyl methacrylate and 0.7 g of divinylbenzene were dropped into it by a peristaltic pump at a flow rate of 2.1 r / min. After the addition was completed, the polymerization reaction was continued for 156 min to obtain an intermediate layer pre-emulsion;
[0113] S9. 6 g of graphene oxide was dispersed in 103 mL of deionized water to obtain a graphene oxide dispersion, and then 8 g of KH-550 was added to 83 mL of anhydrous ethanol, and the dispersion was uniformly dispersed by ultrasonication for 5 min to obtain a silane coupling agent dispersion, and 103 mL of the graphene oxide dispersion and 83 mL of the silane coupling agent dispersion were uniformly mixed by ultrasonication, reacted in an oil bath at 83 ° C for 6 h, and centrifuged for standby use to obtain functionalized graphene;
[0114] S10. The pH of 41 mL of the intermediate layer pre-emulsion was adjusted to 8, 0.16 g of functionalized graphene was added, and the intermediate layer emulsion was obtained after ultrasonic treatment for 42 min;
[0115] S11. 0.5 g of ammonium persulfate was added to 40 mL of the intermediate layer emulsion and 21 g of butyl acrylate, 8 g of methyl methacrylate, 5 g of styrene and 0.9 g of hydroxyethyl methacrylate were added dropwise using a peristaltic pump at a flow rate of 2.1 r / min. After the addition was completed, the polymerization reaction was continued for 156 min to obtain a crosslinker;
[0116] S12. 83 g of an aqueous acrylic resin and 18 g of a core-shell acrylate were mixed to obtain a base emulsion;
[0117] S13. 103 g of the base emulsion, 11 g of a cross-linking agent, 0.8 g of triethanolamine, 0.7 g of a defoaming agent, and 0.6 g of a wetting and dispersing agent were mixed uniformly to obtain a water-based coating based on a modified acrylic resin.
[0118] Embodiment 5: A method for preparing a water-based coating based on a modified acrylic resin, comprising the following steps:
[0119] S1. 8.8 g of methyl methacrylate, 8.8 g of styrene, 0.4 g of divinylbenzene and 48 mL of deionized water were mixed evenly, 0.15 g of sodium dodecyl sulfate was added, pre-emulsified at 74 ° C for 31.5 min at a speed of 298 r / min, and then 0.11 g of ammonium persulfate was added and reacted for 158 min to obtain a mixed solution A;
[0120] S2. 30 g of butyl acrylate and 6 g of isooctyl acrylate were mixed, 1 g of ammonium persulfate was added, and mixed to obtain a mixed solution B;
[0121] S3. 31 g of the mixed solution A was added dropwise to 71 g of the mixed solution B at a flow rate of 2.1 r / min, and the reaction was continued for 158 min after the addition was completed to obtain a core-shell acrylate;
[0122] S4. 84 g of an aqueous acrylic resin and 19 g of a core-shell acrylate were mixed to obtain a base emulsion;
[0123] S5. 0.5 g of nano-silica was added to 13 mL of 80% ethanol aqueous solution, and after being evenly dispersed, 0.043 g of KH570 was added, and then oxalic acid was added dropwise to adjust the pH to 4, and the reaction was carried out at 69 ° C for 118 min, filtered, and washed with ethanol to obtain modified silica;
[0124] S6. 0.3 g of sodium dodecyl sulfate and 0.28 g of OP-10 were mixed to obtain an emulsifier;
[0125] S7. 1.9 g of modified silica, 3.6 g of butyl acrylate, 13 g of styrene and 0.7 g of divinylbenzene were added to 40 mL of deionized water, 0.6 g of emulsifier was added, and pre-emulsified at 69 ° C for 34 min under nitrogen protection to obtain a pre-emulsion, and then 0.7 g of ammonium persulfate was added, and the reaction was carried out at a stirring speed of 296 r / min for 156 min to obtain an inner emulsion;
[0126] S8. 0.3 g of ammonium persulfate was added to 41 mL of the inner emulsion, and 13 g of butyl acrylate, 17.6 g of methyl methacrylate and 0.6 g of divinylbenzene were dropped into the emulsion using a peristaltic pump at a flow rate of 2 r / min. After the addition was completed, the polymerization reaction was continued for 158 min to obtain an intermediate layer pre-emulsion;
[0127] S9. 5 g of graphene oxide was dispersed in 104 mL of deionized water to obtain a graphene oxide dispersion, and then 8 g of KH-550 was added to 84 mL of anhydrous ethanol, and the dispersion was uniformly dispersed by ultrasonic treatment for 6 min to obtain a silane coupling agent dispersion, and 104 mL of the graphene oxide dispersion and 84 mL of the silane coupling agent dispersion were uniformly mixed by ultrasonic treatment, reacted in an oil bath at 85° C. for 7 h, and centrifuged for standby use to obtain functionalized graphene;
[0128] S10. The pH of 42 mL of the intermediate layer pre-emulsion was adjusted to 8.5, 0.18 g of functionalized graphene was added, and the intermediate layer emulsion was obtained after ultrasonic treatment for 46 min;
[0129] S11. 0.4 g of ammonium persulfate was added to 41 mL of the intermediate layer emulsion and 22 g of butyl acrylate, 7 g of methyl methacrylate, 6 g of styrene and 1.2 g of hydroxyethyl methacrylate were added dropwise using a peristaltic pump at a flow rate of 2 r / min. After the addition was completed, the polymerization reaction was continued for 158 min to obtain a crosslinker;
[0130] S12. 84 g of an aqueous acrylic resin and 19 g of a core-shell acrylate were mixed to obtain a base emulsion;
[0131] S13. 104 g of the base emulsion, 11 g of a cross-linking agent, 0.7 g of triethanolamine, 0.6 g of a defoaming agent, and 0.5 g of a wetting and dispersing agent were mixed uniformly to obtain a water-based coating based on a modified acrylic resin.
[0132] Embodiment 6: A method for preparing a water-based coating based on a modified acrylic resin, comprising the following steps:
[0133] S1. 9 g of methyl methacrylate, 9 g of styrene, 0.45 g of divinylbenzene and 50 mL of deionized water were mixed, 0.16 g of OP-10 was added, pre-emulsified at 75 ° C for 32 min at a speed of 300 r / min, and then 0.12 g of ammonium persulfate was added and reacted for 160 min to obtain a mixed solution A;
[0134] S2. 31 g of butyl acrylate and 7 g of isooctyl acrylate were mixed, 1.05 g of ammonium persulfate was added, and mixed to obtain a mixed solution B;
[0135] S3. 32 g of the mixed solution A was added dropwise to 72 g of the mixed solution B at a flow rate of 2.2 r / min, and the reaction was continued for 160 min after the addition was completed to obtain a core-shell acrylate;
[0136] S4. 85 g of an aqueous acrylic resin and 20 g of a core-shell acrylate were mixed to obtain a base emulsion;
[0137] S5. 0.6 g of nano-silica was added to 14 mL of an ethanol aqueous solution having a volume fraction of 82%, and after being evenly dispersed, 0.045 g of KH570 was added, and then oxalic acid was added dropwise to adjust the pH to 4, and the reaction was carried out at 72 ° C for 120 min, filtered, and washed with ethanol to obtain modified silica;
[0138] S6. 0.4 g of sodium dodecyl sulfate and 0.3 g of OP-10 were mixed to obtain an emulsifier;
[0139] S7. 2 g of modified silica, 4.2 g of butyl acrylate, 13.8 g of styrene and 0.9 g of divinylbenzene were added to 42 mL of deionized water, 0.5 g of emulsifier was added, and pre-emulsified at 70 ° C for 35 min under nitrogen protection to obtain a pre-emulsion, and then 0.8 g of ammonium persulfate was added, and the reaction was carried out at a stirring speed of 300 r / min for 160 min to obtain an inner emulsion;
[0140] S8. 0.4 g of ammonium persulfate was added to 42 mL of the inner emulsion, and 14 g of butyl acrylate, 18 g of methyl methacrylate and 0.7 g of divinylbenzene were dropped thereinto by a peristaltic pump at a flow rate of 2.2 r / min. After the addition was completed, the polymerization reaction was continued for 160 min to obtain an intermediate layer pre-emulsion;
[0141] S9. 6 g of graphene oxide was dispersed in 105 mL of deionized water to obtain a graphene oxide dispersion, and then 9 g of KH-550 was added to 85 mL of anhydrous ethanol, and ultrasonically dispersed for 7 min to obtain a silane coupling agent dispersion, and 105 mL of the graphene oxide dispersion and 85 mL of the silane coupling agent dispersion were ultrasonically mixed, reacted in an oil bath at 86° C. for 8 h, and centrifuged for standby use to obtain functionalized graphene;
[0142] S10. The pH of 42 mL of the intermediate layer pre-emulsion was adjusted to 9, 0.2 g of functionalized graphene was added, and the intermediate layer emulsion was obtained after ultrasonic treatment for 50 min;
[0143] S11. 0.6 g of ammonium persulfate was added to 42 mL of the intermediate layer emulsion and 23 g of butyl acrylate, 9 g of methyl methacrylate, 7 g of styrene and 1.35 g of hydroxyethyl methacrylate were added dropwise using a peristaltic pump at a flow rate of 2.2 r / min. After the addition was completed, the polymerization reaction was continued for 160 min to obtain a crosslinker;
[0144] S12. 85 g of an aqueous acrylic resin and 20 g of a core-shell acrylate were mixed to obtain a base emulsion;
[0145] S13. 105 g of the base emulsion, 12 g of a cross-linking agent, 0.8 g of triethanolamine, 0.8 g of a defoaming agent, and 0.6 g of a wetting and dispersing agent were mixed uniformly to obtain a water-based coating based on a modified acrylic resin.
[0146] Comparative Example 1:
[0147] Compared with Example 1, this comparative example does not add core-shell acrylate during the preparation of the base emulsion, and the remaining steps and parameters are the same, which will not be repeated in this comparative example. Finally, a water-based coating based on modified acrylic resin is obtained.
[0148] Comparative Example 2:
[0149] Compared with Example 1, this comparative example only increases the amount of core-shell acrylate from "15g" to "80g", and the remaining steps and parameters are the same, which will not be repeated in this comparative example. Finally, a water-based coating based on modified acrylic resin is obtained.
[0150] Comparative Example 3:
[0151] Compared with Example 1, modified silica was not added in the preparation process of the water-based coating based on modified acrylic resin in this comparative example. The remaining steps and parameters were the same and will not be repeated in this comparative example. Finally, a water-based coating based on modified acrylic resin was obtained.
[0152] Comparative Example 4:
[0153] Compared with Example 1, this comparative example does not add functionalized graphene during the preparation process of the water-based coating based on modified acrylic resin. The remaining steps and parameters are the same and will not be repeated in this comparative example. Finally, a water-based coating based on modified acrylic resin is obtained.
[0154] Comparative Example 5:
[0155] S1. 6 g of methyl methacrylate, 6 g of styrene, 0.15 g of divinylbenzene and 40 mL of deionized water were mixed evenly, 0.11 g of sodium dodecyl sulfate was added, pre-emulsified at 70 ° C for 28 min at a speed of 280 r / min, and then 0.08 g of ammonium persulfate was added and reacted for 150 min to obtain a mixed solution A;
[0156] S2. 26 g of butyl acrylate and 4 g of isooctyl acrylate were mixed, 0.35 g of ammonium persulfate was added, and mixed to obtain a mixed solution B;
[0157] S3. 28 g of the mixed solution A was added dropwise to 68 g of the mixed solution B at a flow rate of 1.8 r / min. After the addition was completed, the reaction was continued for 150 min to obtain a core-shell acrylate;
[0158] S4. 80 g of an aqueous acrylic resin and 15 g of a core-shell acrylate were mixed to obtain a base emulsion;
[0159] S5. 0.3 g of nano-silica was added to 10 mL of 78% ethanol aqueous solution, and after being evenly dispersed, 0.035 g of KH570 was added, and then oxalic acid was added dropwise to adjust the pH to 4, and the reaction was carried out at 68 ° C for 110 min, filtered, and washed with ethanol to obtain modified silica;
[0160] S6. 0.2 g of sodium dodecyl sulfate and 0.2 g of OP-10 were mixed to obtain an emulsifier;
[0161] S7. 1.5 g of modified silica, 1.2 g of butyl acrylate, 10.11 g of styrene and 0.6 g of divinylbenzene were added to 36 mL of deionized water, 0.4 g of emulsifier was added, and pre-emulsified at 65 ° C for 30 min under nitrogen protection to obtain a pre-emulsion, and then 0.5 g of ammonium persulfate was added, and the reaction was carried out at a stirring speed of 280 r / min for 150 min to obtain an inner emulsion;
[0162] S8. 0.2 g of ammonium persulfate was added to 40 mL of the inner emulsion, and 12 g of butyl acrylate, 15.3 g of methyl methacrylate and 0.4 g of divinylbenzene were dropped thereinto by a peristaltic pump at a flow rate of 1.8 r / min. After the addition was completed, the polymerization reaction was continued for 150 min to obtain an intermediate layer pre-emulsion;
[0163] S9. 3 g of graphene oxide was dispersed in 100 mL of deionized water to obtain a graphene oxide dispersion, and then 5 g of KH-550 was added to 80 mL of anhydrous ethanol, and the dispersion was uniformly dispersed by ultrasonication for 5 min to obtain a silane coupling agent dispersion, and 100 mL of the graphene oxide dispersion and 80 mL of the silane coupling agent dispersion were uniformly mixed by ultrasonication, reacted in an oil bath at 78° C. for 6 h, and centrifuged for standby use to obtain functionalized graphene;
[0164] S10. The pH of 38 mL of the intermediate layer pre-emulsion was adjusted to 8, 0.1 g of functionalized graphene was added, and the cross-linking agent was obtained after ultrasonic treatment for 30 min;
[0165] S11. 80 g of an aqueous acrylic resin and 15 g of a core-shell acrylate were mixed to obtain a base emulsion;
[0166] S12. 100 g of the base emulsion, 8 g of the cross-linking agent, 0.5 g of triethanolamine, 0.4 g of the defoaming agent, and 0.3 g of the wetting and dispersing agent were mixed uniformly to obtain a water-based coating based on a modified acrylic resin.
[0167] Performance Testing:
[0168] The water-based coatings prepared in Examples 1 to 6 and Comparative Examples 1 to 5 were poured onto a polytetrafluoroethylene mold and dried at 30° C. for one week to obtain a film;
[0169] The tensile strength and elongation at break of each group of samples were tested according to GB / T 1040.1-2006 standard;
[0170] The impact resistance of each group of samples was tested according to GB / T1732-1993 standard;
[0171] The hardness of each group of samples was tested according to GB / T 6739-2006 standard;
[0172] Carry out salt spray resistance test on each group of samples according to ISO7253 standard, and record the surface status of each group of samples after 800h of salt spray resistance test;
[0173] The damping performance of each group of samples was tested using a dynamic mechanical analyzer, and the damping temperature width (℃) of each group of samples was recorded;
[0174] The water-based coatings prepared in Examples 1 to 6 and Comparative Examples 1 to 5 were coated on tinplate, and after drying, a layer of adhesive was coated on the coating surface. The circular forging die of the adhesion tester was connected to the coating surface through the adhesive. After the adhesive was dried for 24 hours, the excess coating was scraped off along the periphery of the circular forging die. The adhesion tester was used to give the circular forging die a lifting force. When the circular forging die pulled the coating away from the tinplate surface, the value displayed was F. max, the area of the circular forging die is S, the final result is measured three times and the average value is taken. The calculation formula of adhesion is as follows:
[0175]
[0176] The results are shown in Tables 1 and 2:
[0177] Table 1 Summary of experimental results in Examples 1 to 6 and Comparative Examples 1 to 5
[0178]
[0179] Table 2 Summary of experimental results in Examples 1-6 and Comparative Examples 1-5
[0180]
[0181]
[0182] Data Analysis:
[0183] It can be seen from Table 1 and Table 2 above that the water-based coating based on modified acrylic resin prepared by the present invention has stronger mechanical properties, higher hardness, stronger adhesion, stronger salt spray resistance and better damping performance;
[0184] This may be because the core-shell acrylate and water-based acrylic resin provided in the present invention are mixed as the base emulsion, and the core-shell acrylate increases the uniform dispersion inside the system, making the system more stable. At the same time, the presence of a small amount of core-shell acrylate effectively reduces the difficulty of molecular chain movement caused by excessive crosslinking in the system, thereby effectively improving the damping performance of the water-based coating. At the same time, even if the damping performance is increased, the base emulsion and the crosslinking agent are compounded to enhance the synergy, and the presence of multiple aromatic ring rigid groups contained in the crosslinking agent effectively increases the corrosion resistance of the water-based coating. In addition, the present invention introduces an acrylic polymer with a four-layer core-shell structure as a crosslinking agent into the system, and the modified silica in the multi-layer core-shell structure can toughen and modify the water-based coating, and because its surface is sequentially coated with an inner layer, an intermediate layer and an outer layer, the crosslinking agent can be uniformly dispersed in the system without agglomeration in large quantities, and the crosslinking agent of the multi-layer core-shell structure can be crosslinked with the base emulsion inside the system, so the mechanical properties and hardness of the water-based coating can be improved. In addition, the interaction between the compounded base emulsion can also effectively enhance the damping performance, while further improving the corrosion resistance and flame retardancy.
[0185] Those skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of the present invention is limited to these examples. Under the concept of the present invention, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of the different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity.
[0186] The present invention is intended to cover all such substitutions, modifications and variations that fall within the broad scope of the appended claims. Therefore, any omissions, modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A water-based coating based on modified acrylic resin, characterized in that: The method comprises the following raw materials in parts by weight: 100-105 parts of base emulsion, 8-12 parts of cross-linking agent, 0.5-0.8 parts of triethanolamine, 0.4-0.8 parts of defoaming agent, and 0.3-0.6 parts of wetting and dispersing agent; The base emulsion is obtained by mixing water-based acrylic resin and core-shell acrylic ester in a mass ratio of 80-85:15-20; The crosslinking agent is a four-layer core-shell structure, and the four-layer core-shell structure is prepared by a core layer emulsion, an inner layer emulsion, an intermediate layer emulsion and an outer layer emulsion; The core layer emulsion is prepared from modified silicon dioxide; The inner layer emulsion is prepared from methyl methacrylate and styrene; The intermediate layer emulsion is prepared from butyl acrylate, methyl methacrylate and modified graphene; The outer layer emulsion is prepared from butyl acrylate, methyl methacrylate and styrene; The modified graphene is amino-modified graphene oxide.
2. The water-based coating based on modified acrylic resin according to claim 1, characterized in that: The preparation process of the basic emulsion is as follows: Step A1. Methyl methacrylate, styrene, a crosslinking agent and deionized water are mixed evenly, an emulsifier is added, and pre-emulsification is carried out at 70-75° C. for 28-32 minutes at a speed of 280-300 r / min, and then an initiator is added and reacted for 150-160 minutes to obtain a mixed solution A; Step A2. Mix butyl acrylate and isooctyl acrylate evenly, add an initiator, and mix evenly to obtain a mixed solution B; Step A3. Add the mixed solution A dropwise to the mixed solution B at a flow rate of 1.8-2.2 r / min. After the addition is completed, continue the reaction for 150-160 min to obtain a core-shell type acrylate.
3. The water-based coating based on modified acrylic resin according to claim 2, characterized in that, The usage ratio of methyl methacrylate, styrene, crosslinking agent, deionized water, emulsifier and initiator in step A1 is 6-9 g: 6-9 g: 0.15-0.45 g: 40-50 mL: 0.11-0.16 g: 0.08-0.12 g; The cross-linking agent in step A1 is divinylbenzene; The emulsifier in step A1 is any one of an anionic emulsifier and a nonionic emulsifier; The anionic emulsifier is sodium dodecyl sulfate, and the nonionic emulsifier is OP-10; The initiator in step A1 is ammonium persulfate.
4. The water-based coating based on modified acrylic resin according to claim 2, characterized in that: In step A2, the usage ratio of butyl acrylate, octyl acrylate and initiator is 26-31 g: 4-7 g: 0.35-1.05 g; The initiator in step A2 is ammonium persulfate; The mass ratio of the mixed solution A to the mixed solution B in step A3 is 28-32:68-72.
5. The water-based coating based on modified acrylic resin according to claim 1, characterized in that: The preparation process of the cross-linking agent is as follows: Step B1. Add nano-silica to an ethanol aqueous solution, add KH570 after uniform dispersion, and then add oxalic acid to adjust the pH to 4, react at 68-72°C for 110-120min, filter, and wash with ethanol to obtain modified silica; Step B2. Add modified silica, butyl acrylate, styrene and a crosslinking agent to deionized water, add an emulsifier, place at 65-70 ° C for 30-35 minutes under nitrogen protection to obtain a pre-emulsification solution, then add an initiator, and react at a stirring speed of 280-300 r / min for 150-160 minutes to obtain an inner layer emulsion; Step B3. Add an initiator to the inner layer emulsion, and drip butyl acrylate, methyl methacrylate and a crosslinking agent therein using a peristaltic pump at a flow rate of 1.8-2.2 r / min. After the dripping is completed, continue the polymerization reaction for 150-160 min to obtain an intermediate layer pre-emulsion; Step B4. dispersing graphene oxide in deionized water to obtain a graphene oxide dispersion, adding a silane coupling agent to anhydrous ethanol, and dispersing uniformly by ultrasonication for 5-7 minutes to obtain a silane coupling agent dispersion, ultrasonically mixing the graphene oxide dispersion and the silane coupling agent dispersion, reacting in an oil bath at 78-86° C. for 6-8 hours, and centrifuging for standby use to obtain functionalized graphene; Step B5. The pH of the intermediate layer pre-emulsion is adjusted to 8-9, functionalized graphene is added, and the intermediate layer emulsion is obtained after ultrasonic treatment for 30-50 minutes; Step B6. Add an initiator to the middle layer emulsion and drop butyl acrylate, methyl methacrylate, styrene and hydroxyethyl methacrylate using a peristaltic pump at a flow rate of 1.8-2.2 r / min. After the dropwise addition is completed, continue the polymerization reaction for 150-160 minutes to obtain a crosslinking agent.
6. The water-based coating based on modified acrylic resin according to claim 5, characterized in that: The usage ratio of nano-silica, ethanol aqueous solution and KH570 in step B1 is 0.3-0.6 g: 10-14 mL: 0.035-0.045 g; The volume fraction of the ethanol aqueous solution in step B1 is 78%-82%; The amount ratio of modified silica, butyl acrylate, styrene, crosslinking agent, deionized water, emulsifier and initiator in step B2 is 1.5-2g: 1.2-4.2g: 10.11-13.8g: 0.6-0.9g: 36-42mL: 0.4-0.7g: 0.5-0.8g; The cross-linking agent in step B2 is divinylbenzene; The emulsifier in step B2 is obtained by mixing an anionic emulsifier and a nonionic emulsifier in a mass ratio of 0.2-0.4:0.2-0.3; In step B2, the anionic emulsifier is sodium dodecyl sulfate, and the nonionic emulsifier is OP-10; The initiator in step B2 is ammonium persulfate.
7. The water-based coating based on modified acrylic resin according to claim 5, characterized in that: The usage ratio of the inner layer emulsion, initiator, butyl acrylate, methyl methacrylate and crosslinking agent in step B3 is 40-42 mL: 0.2-0.4 g: 12-14 g: 15.3-18 g: 0.4-0.7 g; The initiator in step B3 is ammonium persulfate; The cross-linking agent in step B3 is divinylbenzene.
8. The water-based coating based on modified acrylic resin according to claim 5, characterized in that: The usage ratio of graphene oxide and deionized water in step B4 is 3-6 g: 100-105 mL; The usage ratio of the silane coupling agent and anhydrous ethanol in step B4 is 5-9 g: 80-85 mL; The volume ratio of the graphene oxide dispersion and the silane coupling agent dispersion in step B4 is 100-105:80-85; The silane coupling agent in step B4 is KH-550.
9. The water-based coating based on modified acrylic resin according to claim 5, characterized in that: The ratio of the intermediate layer pre-emulsion to the functionalized graphene in step B5 is 38-42 mL: 0.1-0.2 g; The usage ratio of the intermediate layer emulsion, initiator, butyl acrylate, methyl methacrylate, styrene and hydroxyethyl methacrylate in step B6 is 40-42 mL: 0.3-0.6 g: 16-23 g: 5-9 g: 5-7 g: 0.45-1.35 g; The initiator in step B6 is ammonium persulfate.
10. A method for preparing a water-based coating based on a modified acrylic resin according to any one of claims 1 to 9, characterized in that: The following steps are involved: The base emulsion, the crosslinking agent, the triethanolamine, the defoaming agent and the wetting and dispersing agent are uniformly mixed to obtain a water-based coating based on the modified acrylic resin.
Citation Information
Patent Citations
A silicone-modified waterborne composite wood coating, its preparation method and application
CN109504267B
Preparation method of polyacrylate compound particles for nylon 6 low-temperature toughening modification
CN104356640A
Preparation method of polyacrylate / nano silicon dioxide composite emulsion coating material
CN105273556A
Emulsion with core-shell structure and environment-friendly interior wall coating containing emulsion
CN108484834A
Multilayer core-shell acrylate emulsion as well as preparation method and application thereof
CN116769114A
